SWOT Analysis and SO, ST, WO, and WT Strategies in XYZ E-Commerce - Imanda, Resda Atsila (Dinasti Research, 2022)
E-Commerce XYZ is one of the largest fashion e-commerce pioneers in Southeast Asia that continues to face pressure from local and global competitors. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) faced by e-commerce XYZ in dealing with the dynamic competition in the digital fashion industry. The research method employs a descriptive qualitative approach with literature review as the data collection technique. Initial findings indicate that E-Commerce XYZ's strengths lie in its excellent user experience and robust logistics support, while its weakness is its reliance on discount promotions. Opportunities are abundant through internet penetration and online shopping trends, but threats from social media platforms and direct-to-consumer (DTC) competitors pose significant challenges. This analysis is expected to serve as a foundation for formulating XYZ e-commerce's long-term strategy to maintain its competitive position in the highly competitive online fashion market.